Dramaturgi Kehidupan Pengamen Angklung Jalanan di Jalan Argopuro Kabupaten Jember - Fahmi Hidayat; Velysa Novita Hariyanto; M. Alfandi Amali Husni (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Street Angklung buskers have become a global phenomenon, meaning a phenomenon that we can encounter and is already familiar to us. The presence of these street angklung singers certainly makes motorists curious. Like a theater performance, of course the actors in this performance are angklung singers. In a theatrical performance there are terms front stage and back stage. Front stage is where actors play roles in front of the public, while backstage is what actually happens behind the theater performance. The aim of this research is to reveal street angklung buskers playing the role of actors and the research method used in this research is an ethnographic approach. The results of this research are that a street angklung busker on Jalan Argopuro started out as an ordinary angklung busker but in reality he was also a member of a silat organization called the Brotherhood of Loyal Heart Terate.